Estimating the Water Supply Function in Secondary and Productivity Markets, Case Study: Qazvin Water Share Market - Seyedeh Marziye Hosseini; Hamed Mazandarani Zadeh; Hamid Azizmohammadlou; Mohammad Mahjoub (تحقیقات منابع آب ایران, 2025)
The increase in population, the occurrence of droughts and the uncontrolled extraction of groundwater resources have limited water resources. One of the new topics in water resource management is the formation of the water market, which is used as a tool for reallocating Water Resources. In order to increase productivity and manage water resources, the water rights market in Qazvin province has been piloted since March, 2023. The aim of this study is to examine the water supply mechanism in the water right market and estimate the supply function in secondary markets and productivity. The secondary market is a market in which suppliers and applicants are both from the agricultural sector and the productivity market is a market where suppliers-from the agricultural sector and applicants from the industrial sector. To estimate the supply function, the principles of microeconomics and the Ordinary least squares regression method have been used. The supply function was estimated using information including the volume and selling price of water traded in the market, production costs, well depth, operating hours, technologies used including pump type and irrigation system type, annual water right amount and cultivation area from July 2023 to December 2024. The price coefficient in the productivity market was estimated at 0.277 and 2.046 in the secondary market. The negative price elasticity of supply in the secondary market indicates the existence of risk for farmers to enter the secondary market, and this risk can cause the unwillingness of farmers to enter the secondary market.